Urgency Analysis of Pet Regulation as Subject of Legal Protection - Anadi, Yandri Radhi; Suhartono, Slamet; Mangesti, Yovita Arie; Prasetyawati, Endang; Cikusin, Yaqub (Universitas Medan Area, 2025)
This study analyzes the urgency of regulating pets as a subject of legal protection in Indonesia. Although pets have the right to be treated humanely, regulations in Indonesia do not specifically recognize pets as legal subjects entitled to legal protection. This study uses a normative juridical approach with an analytical descriptive method to examine regulatory gaps related to pet protection. Data was obtained through literature studies on laws and regulations, legal doctrines, and cases of violence against pets. The results of the study show that existing regulations, such as Criminal Code Article 302 and Law No. 18 of 2009, still focus on the health aspect of livestock and have not accommodated the basic rights of pets. In addition, criminal sanctions for perpetrators of violence against pets are considered ineffective in providing a deterrent effect. This study recommends the establishment of a special law on the protection of pets, a revision of the Criminal Code Article 302, and public education programs to increase awareness about pet rights. The implementation of these regulations is expected to strengthen legal protection for pets and encourage a paradigm shift in society in treating pets as legal subjects who are entitled to protection.